Clinicopathological assessment of intramammary administration of genetically engineered Salmonella Agona (4KA32) in domestic dogs - Rajendren, Sujey Kumar (2017)
Salmonella is a good bacterial candidate for anti-cancer therapy because of its characteristics such as motile, facultative anaerobiosis, and the ability to invade epithelial cells and engineered auxotrophies. Salmonella enterica serovar Agona is less pathogenic compared to Salmonella enterica serovar Typhimurium. Salmonella enterica serovar Agona can be genetically engineered to reduce further its pathogenic effects on hosts by eliminating the virulence genes of SopB and SopD. Genetically engineered Salmonella enterica serovar Agona (4KA32) was tested on mice model and showed 100% survival rate over two months period. The pathogenicity of 4KA32 in dogs are undefined. The objectives of this research are to determine the preliminary clinical and pathological effects of intra-mammary administration of 4KA32 in seven experimental domestic healthy dogs. Dogs were subjected to either single or repeated dosing over three weeks and euthanized at the end of study period for histopathology evaluation. 4KA32 was administered at various concentrations from 1×106 CFU/mL to 1×109 CFU/mL for both single and repeated dosing. There was significant increase (p < 0.05) of monocyte count across all the dogs at Day 1 and persisted until the end of the study. The monocyte count of dog injected higher doses decreased significantly (p < 0.05) when compared to monocyte count of dog injected with dose 1×106 CFU/mL. There was significant increase (p < 0.05) of neutrophils count across all the dogs at Day 1 which persisted until Day 4. The neutrophil count of dogs injected with single dose of 1×108 CFU/mL and 1×109 CFU/mL showed significant neutrophilia compared to single dose 1×106 CFU/mL. The neutrophils count of dogs injected with repetitive dose of 1×107 CFU/mL and 1×109 CFU/mL significantly increased compared neutrophils count of dogs injected with dose 1×106 CFU/mL. Lymphocytosis was not observed in dogs injected with repetitive dose of 4KA32. Whereas, dogs injected with single dose of 4KA32 showed significant lymphocytosis (p < 0.05) on Day 4 only. Comparing lymphocyte count across the concentration, dogs injected with single dose of 1×106 CFU/mL of 4KA32 showed lymphocytosis and lymphocyte count for higher doses significantly decreased (p < 0.05). Serial faecal and blood samples were cultured negative for 4KA32 growth. All dogs demonstrated superficial inflammation and swelling on the injected sites which healed naturally by Day 3. The highest concentrations of 4KA32 at 1×109 CFU/mL resulted in formation of superficial ulceration on Day 5 that gradually healed within seven days. None of the dogs developed fever or systemic signs including diarrhoea or inappetance during the experimental observation. Histopathology analysis revealed, mild to moderate infiltration of inflammatory cells on mammary gland of dogs injected with dose 1×106 CFU/mL to 1×108 CFU/mL. Severe infiltration of inflammatory cells was observed with dog injected with dose 1×109 CFU/mL of 4KA32. Histopathology of intestine revealed dog injected with 1×107 CFU/mL developed mild to moderate ulceration whereas dog injected with 1×109 CFU/mL developed moderate to severe ulceration. This study provides evidence that 4KA32 has minimal to none systemic pathogenic effects with potential to induce local inflammation in mammary tissues. Detection of 4KA32 isolates within the lung, mesenteric lymph node and kidney without pathogenic lesions suggest that this bacteria can have potential to target metastasis of cancer cells which is common to these sites. Other tissues were negative for 4KA32. There was minimal pathogenicity observed in all the dogs injected with 4KA32. This suggest that 4KA32 is safe to be administered in dogs.